The eﬀects of low-level laser therapy in De Quervain tenosynovitis: evidence from a systematic review and meta-analysis - de-la-Barra-Ortiz, Hernán Andrés; De La Maza, Tomás Chavalos; Gascón-Madrid, María Jesús; Hormazábal-Cerda, Gabriela; Meza-Arellano, Alexis; Chamorro-Lange, Claudio (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. De Quervain tenosynovitis (QT), a painful and inﬂammatory wrist condition, presents challenges in its conserva-tive treatment. Although low-level laser therapy (LLLT) is considered an attractive option, the evidence of its eﬀectiveness requires evaluation. This systematic review aimed to assess the analgesic eﬀects of LLLT in QT patients.Methods. The search used the PubMed, Scopus, Web of Science, Embase, EBSCOhost, Physiotherapy Evidence Database (PEDro), and Google Scholar (last updated on March 10, 2025) databases to identify clinical trials comparing the eﬀects of LLLT to other physical therapy or medical treatments in patients with QT. The primary outcomes evaluated were pain intensity, grip strength, and disability. The Cochrane Risk of Bias Tool 2 (RoB2) assessed study quality, and the meta-analysis used weighted mean diﬀerence (WMD) or standardised mean diﬀerence (SMD). Evidence-based recommendations for statistically signiﬁcant outcomes were presented following the GRADE approach.Results. Eight studies were included, with an overall low risk of bias (RoB) (25%). Deviations from intended interventions and outcome measurement were sources of bias. Post-treatment pain intensity was statistically signiﬁcant for LLLT (WMD = –0.98 cm; 95% CI: –1.91, –0.04; p = 0.04; LLLT group [107], control group [124]). RoB and heterogeneity rated the evidence certainty as very low yet important. Handgrip strength and synovial sheath thickness were not statistically signiﬁcant between groups (p > 0.05).Conclusions. LLLT reduces pain eﬀectively. Prioritising LLLT or ultrasound (US) over invasive treatments may optimise clinical management and minimise postsurgical complications.
Keywords: laser therapy; low-level light therapy; musculoskeletal pain; de Quervain disease; tenosynovitis